Driving frugal innovation in SMEs: how sustainable leadership, knowledge sources and information credibility make a difference - Ur Rehman, Khalil; Anwar, Rana Salman; Antohi, Valentin Marian; Ali, Uzma; Fortea, Costinela; Laura Zlati, Monica (Frontiers in Sociology, 2024)
This study investigates the driving factors behind frugal innovation in Small and Medium-sized Enterprises (SMEs). It specifically examines sustainable leadership as an independent variable, considering its impact on frugal innovation, with sources of knowledge mediating this relationship and information credibility moderating the effects. Employing a Partial Least Squares Structural Equation Modeling (PLS-SEM) approach, data were gathered from 325 employees of SMEs in Pakistan. This methodology was chosen for its ability to handle complex relationships between multiple variables simultaneously, offering robust insights into the interplay among sustainable leadership, sources of knowledge, information credibility, and frugal innovation. The results reveal significant associations between sustainable leadership, sources of knowledge, information credibility, and frugal innovation. Sustainable leadership demonstrates a substantial influence on both sources of knowledge and frugal innovation. Furthermore, sources of knowledge play a vital role in mediating the relationship between sustainable leadership and frugal innovation. Information credibility emerges as a significant moderator, affecting the pathways between sustainable leadership, sources of knowledge, and frugal innovation. The findings underscore the importance of sustainable leadership and credible information sources in driving frugal innovation within SMEs. They highlight the intricate interdependencies among these variables and emphasize the pivotal role of information credibility in shaping these dynamics. These results carry significant implications for SMEs in Pakistan, shedding light on the mechanisms through which sustainable leadership and reliable knowledge sources can stimulate frugal innovation in emerging economies.